Skin Care and Women's Identity: The Role of Digital Media in the Formation of Self-Confidence - Teguh Purnomo (PUTRA JAWA PUBLISHER, 2025)
The use of skincare is not only a part of self-care, but also forms the identity and self-confidence of women in the digital era. Digital media plays a significant role in shaping perceptions and standards of beauty through the content consumed daily (Tiggemann & Zaccardo, 2018). Exposure to beauty influencers, skincare product advertisements, and beauty trends on social media influence the construction of women's identity and increase the drive to meet ideal beauty standards (Perloff, 2014). This phenomenon is closely related to the concept of self-objectification, where women begin to judge themselves based on external standards displayed by digital media (Moradi, 2010). Studies show that regular use of skincare, influenced by digital media, can increase self-confidence because of feelings of better appearance (McNeill & Venter, 2019). Thus, digital media becomes an important mediator in the relationship between the use of skincare and the formation of women's self-confidence in the modern era.